Estimasi sebaran konsentrasi total suspended solid (TSS) di Tahura Ngurah Rai Denpasar tahun 2016 dan 2020 - Rejeki, Ketut Listyani Sri; Putra, I Dewa Nyoman Nurweda; Nuarsa, I Wayan (Journal of Marine and Aquatic Sciences; Vol 9 No 1 (2023), 2023)
The large number of mangrove land conversions can cause various impacts, such as causing coastal abrasion to affect sedimentation rates. One of the variables used to determine the level of pollution and sedimentation that occurs in aquatic ecosystems is Total Suspended Solid (TSS). Based on research conducted by Sebastian (2020), mangrove land cover in Tahura Ngurah Rai decreased by 25.58 hectares in 2016 - 2020 due to the mass mortality of mangroves in 2019. The decline in mangrove land in this location allows an increase of TSS in the surrounding waters due to the lack of mangroves which function as a barrier and sediment trap. One of the satellite that have been widely used in observing the distribution of TSS concentrations is the Landsat-8 OLI. Therefore, researchers are interested in knowing the changes in TSS concentrations that occurred in Tahura Ngruah Rai in 2016 and 2020 using Landsat 8 imagery. This study used a gravimetric method to analyze TSS concentrations in situ at 45 sample points carried out by random sampling. To find out the spatial estimation of TSS in 2016 and 2020, an empirical algorithm is used. The best TSS estimation model in this study is the combination of the blue band/ SWIR-1 band using linear equations. The processing results show the concentration of TSS in 2016 has a range between 66 mg/L to 264 mg/L with an average of 127.74 mg/L, while . In 2020 TSS has a range between 72 mg/L to 209 mg/L with an average of 133.04 mg/L.